Effect of establishment methods and nutrient management on biochemical attributes, grain quality, yield parameters and yield of rice (Oryza sativa L.) in coastal Odisha - Budhia, AK; Panda, R K; Garnayak, L M; Nayak, RK; Samant, T K (ORYZA-An International Journal of Rice, 2021)
A field experiment was conducted during kharif season of 2019 at Agronomy Main Research Farm, Odisha University of Agriculture and Technology, Bhubaneswar to study the effect of establishment methods and nutrientmanagement on biochemical attributes, grain quality, yield parameters and yield of rice. The experiment comprised of two rice establishment methods, viz. direct seeded (DSR) and transplanted (TPR) and three nutrient management practices, viz. inorganic (soil test based fertilizer recommendation (STBFR), organic (1/3rd N through green manuring + 1/3rd N through neem oil cake + 1/3rd N through vermicompost) and integrated nutrient management (50% through STBFR + 50% through green manuring) laid out in a randomised blockdesign with three replications. The results indicated that the concentration of chlorophyll was maximum at vegetative and gradually decreased up to maturity stage. TPR recorded comparatively higher total chlorophyll content (2.91mg g-1), grain C (40.58%), H (6.98%), S (0.18%), C/N (36.54), panicles hill-1 (6.78), panicle weight hill-1 (27.05 g), 1000 grain weight (27.86 g), number of filled grains panicle-1 (176.60) with 18.3 % yield advantage over DSR. Among nutrient management, INM recorded higher S (0.17%), carbohydrate (17.82%),panicle numbers hill-1 (8.5), panicle weight hill-1 (30.19 g), 1000 grain weight (28.13 g), number of filled grains panicle-1 (187.89), grain yield (4.36 t ha-1) with harvest index (39.67%), where as maximum N (1.48%), C (41.58%), H (7.07%), S(0.18%), C/H (5.87) was obtained in inorganic with grain yield (3.78 t ha-1). Organic produced the highest chlorophyll total (2.72 mg g-1), C/N (37.89) and harvest index (36.72%) with minimum grain yield (3.74 t ha-1). Hence, organic in conjunction with chemical ferilisers under TPR not only  enhances the growth and yield but also improvement of biochemical attributes and grain quality of rice in coastal Odisha.